Chemical profile of herbs using fourier-transform infrared spectroscopy (FT-IR) and thin layer chromatography (TLC) / Intan Farhana Ismail - Ismail, Intan Farhana (2014)
This research deals with mainly these three types of plants, which are Strobilanthes crispus, Pereskia bleo and Brucea javanica, in which the main objectives is to determine the chemical profile obtained from the methanolic extraction yield from these plants. The purposes of this study are to determine whether the chemical profiles of these herbs are different, and to observe the differences in chemical profile of these herbs using Fourier Transform Infrared Spectroscopy {FT-IR) and Thin Layer Chromatography (TLC). In Fourier Transform Infrared Spectroscopy {FT-IR) method, the prepared sample is place in the sample compartment for analysis to obtain the required spectrum. For Thin Layer Chromatography (TLC) method, retention factor (Rf) value is used to indicate the compounds present in the sample. TLC experiment is done to see the separation of bands between the plants and their differences in pattern by using 'trial and error' of different solvent system. For FT IR, the infrared spectra can be seen and compared between these three plants to see the similarities and differences. Pereskia bleo and Brucea javanica have almost the same spectra while Strobilanthe scrispus are different from the other two plants.